1998
DOI: 10.1200/jco.1998.16.4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy versus radiotherapy in patients with advanced nasopharyngeal cancer: phase III randomized Intergroup study 0099.

Abstract: We conclude that chemoradiotherapy is superior to radiotherapy alone for patients with advanced nasopharyngeal cancers with respect to PFS and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

49
1,464
13
29

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,064 publications
(1,555 citation statements)
references
References 30 publications
49
1,464
13
29
Order By: Relevance
“…One of the main reasons for the increase in survival rates for NPC patients was the introduction of concomitant chemo-radiotherapy and the use of intensity-modulated radiotherapy. In 1998 Al-Sarraf et al found improvement in survival for patients with advanced NPC receiving chemo-radiotherapy compared to radiotherapy alone [19] and later this was verified in a Cochrane review [20]. Although the overall survival in Greenland has improved significantly, it is still not comparable to Denmark or the United States.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for the increase in survival rates for NPC patients was the introduction of concomitant chemo-radiotherapy and the use of intensity-modulated radiotherapy. In 1998 Al-Sarraf et al found improvement in survival for patients with advanced NPC receiving chemo-radiotherapy compared to radiotherapy alone [19] and later this was verified in a Cochrane review [20]. Although the overall survival in Greenland has improved significantly, it is still not comparable to Denmark or the United States.…”
Section: Discussionmentioning
confidence: 99%
“…( Al-Sarraf et al, 1998;Lin et al, 2003;Wee et al, 2004). Thus, with reanalysis, we have eliminated the bias with the use of chemotherapy and make the two cohorts more comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high rate of systemic relapse, chemotherapy has been incorporated into the primary treatment of locally advanced disease in order to improve the outcome. Concurrent chemoradiotherapy was shown to improve overall and progression-free survival for locally advanced NPC in the Intergroup study (Al-Sarraf et al, 1998) and this was replicated in studies carried out in the endemic areas of Singapore (Wee et al, 2004), Hong Kong and Taiwan (Lin et al, 2003). However, a significant proportion of patients would still relapse systemically despite combined modality therapy and many of these patients would ultimately succumb to disseminated disease.…”
mentioning
confidence: 87%
“…Given its anatomical location and the proximity to critical organs, radiation therapy (RT) is the primary local modality in contrast to other head and neck malignancies where surgery may still play a major role. As such, prior to the advent of megavoltage RT, NPC had a poor prognosis; however, modern RT technology, especially Intensity Modulated RT, and concurrent chemotherapy has resulted in >70% 5‐year overall survival 2, 3, 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the early 1990s and 2000s demonstrated that concurrent chemoradiation (CRT) followed by adjuvant cisplatin improved survival compared to RT alone and established this as the standard of care for newly diagnosed NPC 2, 5. Furthermore, the use of 3‐dimensional imaging (CT and MRI) along with improvement in RT technology has resulted in excellent local control rates 6.…”
Section: Introductionmentioning
confidence: 99%